Static and Dynamic Loads in Ore and Waste Rock Passes in Underground Mines - M. Beus; R. Iverson; A. Dreschler; V. Scott (The National Institute for Occupational Safety and Health (NIOSH))
This paper describes research to improve safety during transport of ore and waste in underground mines. Field tests are underway in mines in Idaho and Montana. Strains measured on structural support members in an ore pass provided information about total forces acting on the structure as material was dumped into it. Results show that measured static loads were considerably less than actual total weight of the material dumped and that dynamic loads were subject to many factors, such as effects of blasting to remove hang-ups. Comparisons of measurements and computer results using a particle flow code indicated that several difficulties remain before achieving realistic determinations and models of the dynamic effects of particle flow in ort: passes and impact loads on the gates. Impact loads were overestimated in computer analyses as compared to loads measured in field tests. An alternative design approach based on softening the chute and control gate assembly is being proposed.